METODE DAKWAH USTADZ RAHMAT AFIFI DALAM MENYIARKAN AGAMA ISLAM TERHADAP JAMA’AH DI MASJID RAUDHATUL MUTTAQIN KOTA DUMAI - Devi Anggraini; Desi Syafriani (ADISAM PUBLISHER, 2023)
Da'wah is the process of spreading Islamic teachings to mankind, and always using different methods depending on the situation and circumstances. Da'wah is no longer a strange thing in everyday life, because since the time of the Prophet Muhammad it has been recommended and stipulated that humans must preach, even if they only convey one verse. The development of Islamic da'wah always follows the times, therefore for maximum and effective da'wah success various supporting factors are needed, including the correct da'wah method so that the da'wah delivered is on track. The da'wah method is very necessary in the delivery of da'wah so that the da'wah delivered can be accepted and applied easily by mad'u. The type of research used is field research with a descriptive qualitative approach, namely research in which the data collection method is obtained from observation, interviews and documentation. Data analysis techniques systematically select data obtained from interviews and documentation.